A train-the-trainer design for green ambassadors in an environmental education programme on plastic waste recycling. Issue 1 (2nd January 2018) - Cheung, Yannes Tsz-Yan; Chow, Cheuk-Fai; So, Winnie Wing-Mui
ABSTRACT: To educate a sustainable future, a train-the-trainer (TTT) approach was adopted to train student teachers (STs) from a teacher education institute to be green ambassadors (GAs) in an environmental education (EE) programme with the aim of promoting plastic waste recycling among primary school pupils. The design of the TTT course for the GAs not only focused on the input of subject matter knowledge, but also on pedagogical practices to help them develop pedagogical content knowledge (PCK) for effective teaching. The GAs were interviewed to find out their PCK understanding after the programme. The features related to PCK identified in this study can be used to inform TTT design, which is important for educators in the future development of GAs in EE programmes.